Who compares to whom? The anatomy of income comparisons in Europe - Andrew E. Clark; Claudia Senik (Institute for the Study of Labor (IZA), 2009)
This paper provides unprecedented direct evidence from large-scale survey data on both the intensity (how much?) and direction (to whom?) of income comparisons. Income comparisons are considered to be at least somewhat important by three-quarters of Europeans. They are associated with both lower levels of subjective well-being and a greater demand for income redistribution. The rich compare less and are more happy than average when they do, which latter is consistent with relative income theory. With respect to the direction of comparisons, colleagues are the most frequently-cited reference group. Those who compare to colleagues are happier than those who compare to other benchmarks; comparisons to friends are both less widespread and are associated with the lowest well-being scores. This is consistent with information effects, as colleagues' income arguably contains more information about the individual's own future prospects than do the incomes of other reference groups. Last, there is some evidence that reference groups are endogenous, with individuals tending to compare to those with whom they interact the most often.
urn:nbn:de:101:1-200910122556
Keywords: D31; D63; I3; J31; Z13; 330; Income comparisons; relative income; reference groups; happiness; redistribution; European Social Survey; Einkommensverteilung; Meinung; Informationsverhalten; Vergleich; Lebenszufriedenheit; EU-Staaten